Entrepreneurial Team Regulatory Focus: The Case of Early Growth in a Sustainable Venture - Hermans, Julie; Ben-Hafaïedh, Cyrine (Management international / International Management / Gestiòn Internacional, 2020)
We explore the emergence of an entrepreneurial team strategic orientation, or team regulatory focus, and highlight factors that contribute to its dynamism throughout a sustainable venture’s early growth. By considering the hierarchical model of regulation that distinguishes between the system (ideal vs. ought goals), strategic (eager vs. vigilant), and tactical (risky vs. conservative) levels, we show that the combination of foci is achieved at the tactical level, when team members have reached a shared understanding at the strategic level. Moreover, changes at the strategic level can accompany changes at the goal level, pressuring ideal goals that were previously shared.